Tackling Cyberbullying Crimes to Reduce the Phenomenon of Violence - Bouragba, Mostefa; Alexandre, Dennis (جامعة زيان عاشور الجلفة, 2024)
Cyberbullying has emerged because of the dramatic advances in technology, the rapid increase in electronic communications and the consequent dramatic development, misuse and lack of control over different means of communication cyberbullying has emerged and threatens a large part of society, starting attention to it and working to combat it and tackle it as a crime that has begun to be considered a long term phenomenon, until it is recognized as a form of violence. The risks of cyberbullying are reflected in its content. The use of derogatory language and abusive rumours spread as soon as they were transmitted at lightning speed. They also hack personal accounts on social media sites, steal photos and personal data and post them on other people's accounts. As a result, the victim is alienated from the same act or behaviour, creating a state of congestion and anger among members of society. Cyberbullying is therefore a form of direct violence. How effective is the law to address cyberbullying in reducing violence in society?
Keywords: التنمر الإلكتروني -- مواقع التواصل الاجتماعي -- السلوك العدواني -- ظاهرة العنف -- الجرائم الإلكترونية